Does the exposure to authentic materials increase the listening skill of the students from the Advanced Intensive English I, second semester 2013 at the Foreign Language Department in the University of El Salvador? - Bermudez Alfaro, Victoria Esmeralda; Hsiao, Chuan Wei (2024)
Listening is a skill that takes practice to improve one´s overall proficiency in the English language. It is believed that listening is one of the most difficult skills to develop due to the different accents and pronunciations around the world. Mark Murphy states that this skill seems to be so simple, yet the average person retains only 10% of what they hear. Even though it is the key to all effective communication, without the ability to listen to messages effectively ideas may be easily misunderstood, communication breakdowns may be possible, and the sender of the message can easily become frustrated or irritated. It is important to take into account that problems in communication may be caused by different factors and that is why it is important to clarify the difference between listening and hearing. Hearing refers to the sounds people perceive, whereas listening requires more than that: it requires focusing. Listening means paying attention not only to the story, but it also requires paying attention to some other details. For example, it is important to identify how something is told, the use of language and voice, and how the other person uses his or her body. In other words, it means becoming aware of both verbal and non-verbal messages. People`s ability to listen to messages effectively depends on the degree to which you perceive and understand them. “The most basic and powerful way to connect to another person is to listen. Just listen. Perhaps the most important thing we ever give each other is our attention.” Rachel Naomi Remen (2005)